DOI: 10.31274/rtd-180813-2417
|View full text |Cite
|
Sign up to set email alerts
|

Manifest dream content of adolescents

Abstract: Thés material was produced from a microfilm copy of the original document. While the most advanced technological means to photograph and reproduce this document have been used, the quality is heavily dependent upon the quality of the original submitted. The following explanation of techniques is provided to help you understand markings or patterns which may appear on this reproduction. 1.The sign or "target" for pages apparently lacking from the document photographed is "Missing Page(s)". If it was possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 86 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…These present results indicate that it is feasible to collect Most Recent Dreams from young middle-class teenagers within the time frame of a standard classroom period. The fact that more girls than boys provided reports is consistent with findings on greater recall by girls in the laboratory (Strauch, 1996) and with the larger number of dreams reported by girls in dream diaries (Howard, 1978; Strauch & Lederbogen, 1999; Winegar & Levin, 1997).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…These present results indicate that it is feasible to collect Most Recent Dreams from young middle-class teenagers within the time frame of a standard classroom period. The fact that more girls than boys provided reports is consistent with findings on greater recall by girls in the laboratory (Strauch, 1996) and with the larger number of dreams reported by girls in dream diaries (Howard, 1978; Strauch & Lederbogen, 1999; Winegar & Levin, 1997).…”
Section: Discussionsupporting
confidence: 84%
“…The lack of a reliable and feasible method for collecting large and representative samples of dream reports in an efficient way is one of the major obstacles to the systematic study of dream content. For example, only a small percentage of teenagers asked to keep dream journals for one or two weeks on a voluntary, unpaid basis are likely to record five or more dreams, with boys providing even fewer dreams than girls (e.g., Buckley, 1970; Howard, 1978; Winegar & Levin, 1997), and there are inevitable questions about whether those who record their dreams differ from those who do not (Domhoff, 1999). Then, too, if participants are not recalling very many dreams while keeping a journal, they may be tempted to report recurrent dreams or memorable childhood dreams that are not likely to be typical of dream life.…”
mentioning
confidence: 99%
“…First, the problems of the dream-diary method are probably magnified in studies of younger age groups (Foulkes, 1979). Both Bulkley (1970) and Howard (1978) reported difficulties in obtaining completed diaries, especially from boys. In their study of the maturity of interpersonal relations in the dreams of adolescents, Winegar and Levin (1997) had 182 initial volunteers out of the 550 students in the classrooms they visited, but only 115 turned in at least two dreams of 35 words or more; 63% of their final sample were girls, 37% boys.…”
Section: A New Approach To Collecting Dream Reportsmentioning
confidence: 99%
“…Since then, a large body of research has further examined gender differences in dreams (Domhoff, 1996; Domhoff & Schneider, 2008; Hall, Domhoff, Blick, & Weesner, 1982; Hall & Van de Castle, 1966; Howard, 1978; Krippner & Weinhold, 2002; Krippner, Winkler, Rochlen, & Yashar, 1998; Rubenstein & Krippner, 1991; Schredl, Ciric, Bishop, Gölitz, & Buschtöns, 2003; Schredl & Piel, 2003). The Richmond Study, conducted 30 years after the normative study, demonstrated that the gender differences and similarities found in the normative study had remained stable over 30 years, despite sociological and social role changes (Hall et al, 1982).…”
Section: Normative Studies Conducted In the United Satesmentioning
confidence: 99%